Well‐Paired‐Seq: A Size‐Exclusion and Locally Quasi‐Static Hydrodynamic Microwell Chip for Single‐Cell RNA‐Seq. Issue 7 (6th May 2022) - Yin, Kun; Zhao, Meijuan; Lin, Li; Chen, Yingwen; Huang, Shanqing; Zhu, Chun; Liang, Xuan; Lin, Fanghe; Wei, Haopai; Zeng, Huimin; Zhu, Zhi; Song, Jia; et al.
Abstract: Single‐cell RNA sequencing (scRNA‐seq) is a powerful technology for revealing the heterogeneity of cellular states. However, existing scRNA‐seq platforms that utilize bead‐based technologies suffer from a large number of empty microreactors and a low cell/bead capture efficiency. Here, Well‐paired‐seq is presented, which consists of thousands of size exclusion and quasi‐static hydrodynamic dual wells to address these limitations. The size‐exclusion principle allows one cell and one bead to be trapped in the bottom well (cell‐capture‐well) and the top well (bead‐capture‐well), respectively, while the quasi‐static hydrodynamic principle ensures that the trapped cells are difficult to escape from cell‐capture‐wells, achieving cumulative capture of cells and effective buffer exchange. By the integration of quasi‐static hydrodynamic and size‐exclusion principles, the dual wells ensure single cells/beads pairing with high density, achieving excellent efficiency of cell capture (≈91%), cell/bead pairing (≈82%), and cell‐free RNA removal. The high utilization of microreactors and single cells/beads enable to achieve a high throughput (≈10 5 cells) with low collision rates. The technical performance of Well‐paired‐seq is demonstrated by collecting transcriptome data from around 200 000 cells across 21 samples, successfully revealing the heterogeneity of single cells and showing the wide applicability of Well‐paired‐seq for basic and clinical research. Abstract : A high‐throughput and cost‐effective single‐cell RNA sequencing method (Well‐paired‐seq) for revealing the heterogeneity of single cells in complex systems. Based on size exclusion and quasi‐static hydrodynamic principles, Well‐paired‐seq achieves excellent efficiency of cell capture (≈91%), cell/bead pairing (≈82%), cell‐free RNA removal, and a high throughput (≈10 5 cells).